(untitled) (The International Journal of Educational Sciences and Arts, 2026)
The current study aims to identify the risks of online exploitation of children and the ways to protect them amid the dominance of digital media, in addition to assessing parents’ awareness of the impact of digital media on their children and exploring the challenges they face in safeguarding them from online exploitation. The researcher employed a survey methodology using an electronic questionnaire (Google Form) to collect data from a randomly selected sample of 325 parents, aiming to measure their opinions regarding the online exploitation of children and protective measures in the context of digital media dominance. The study was grounded in the compensatory internet use model and revealed several key findings, most notably that the vast majority of parents believe parental monitoring effectively reduces the risks of online exploitation, reflecting a high level of family awareness regarding the importance of continuous oversight of children’s digital activity and its role in enhancing protection and prevention against online threats. Additionally, most parents perceive that excessive internet use by their children helps fulfill certain psychological needs, indicating their recognition of the psychological role the internet may play in children’s lives.